Detection of porcine circovirus‐like virus P1 in Hebei, China. Issue 5 (14th May 2018) - Wen, L.; Mao, A.; Jiao, F.; Zhang, D.; Xie, J.; He, K.
Summary: Porcine circovirus‐like virus P1 is a novel unclassified circovirus that was first detected in China and may be associated with post‐weaning multisystemic wasting syndrome (PMWS) and congenital tremor. In this study, we detected P1 infection in pigs in Hebei Province, China, in 2017. One hundred and forty of 500 (28.0%) serum samples from 25 pig farms with different PMWS status in seven cities were P1 positive on PCR. Twelve P1 strains were sequenced, and the complete genomes of 11 P1 strains were 648 nucleotides (nt) in length, whereas that of strain ZJK02 was 647 nt, with a G deletion at position of 183 in its genome. The complete genomic and capsid protein sequences of the 12 P1 strains analysed in this study shared 98.8%–100.0% and 86.5%–100.0% identity, respectively. A phylogenetic analysis based on the complete genomic and capsid sequences of 26 P1 strains showed that the 12 P1 sequences from Hebei Province clustered on two small branches. Further studies of the evolution and pathogenesis of P1 are required.